The Influence of Reward and Punishment Method on Students English Learning at MTA Islamic Boarding School: Pengaruh Metode Reward dan Punishment terhadap Motivasi Belajar Bahasa Inggris Santri Pondok Pesantren MTA - Annisa, Miftahul Ulum; Muttaqin, Syariful; Sugiharti, Eni (EDUCAFL: Journal on Education of English as Foreign Language, 2024)
Education in Islamic boarding schools in Indonesia is vital for deepening religious knowledge and developing other skills, such as bilingual abilities. To enhance motivation, reward and punishment methods based on behaviorism theory can be used. This study examines how rewards and punishments affect English learning motivation at MTA Al-Amien Prenduan Islamic Boarding School. Using a quantitative approach, the study involved 100 students chosen from a group of 961 through cluster sampling. Data was collected with a reliable and valid questionnaire and analyzed with classical assumption tests. Linear regression was used to explore the relationship between rewards, punishments, and student motivation. The results showed that both rewards and punishments significantly impact student motivation (p < 0.05). Specifically, the t-test values for both rewards and punishments were 4.071, higher than the t-Table value of 1.661. The F test also confirmed that rewards and punishments together have a significant effect on motivation (F = 27.660, p < 0.05). This study provides both theoretical insights into the role of rewards and punishments in education and practical recommendations for educators. The findings can help in creating effective strategies and policies to enhance student performance in language and religious education in Islamic boarding schools. Keyword: Reward, Punishment, Learning Motivation